Women and Money: Unique Issues – Money and the Family - Lynda Spence; Martie Gillen; Diann Douglas (EDIS, 2013)
Ask any parent and he or she will tell you — it costs money to raise children. Taking into account inflation, a middle-income family may spend more than $295,000 to raise a child born in 2011 to the age of 17. This is not a small amount of money, so you will need to know the types of expenses required to raise your family. This 5-page fact sheet reviews the costs associated with raising children and gives you tips on how to teach your children about finances. By knowing the costs of raising your family and setting up a budget, you can teach your children money management skills that will help them throughout their lives. Written by Lynda Spence, Martie Gillen, and Diann Douglas, and published by the UF Department of Family Youth and Community Sciences, March 2013.